2021
DOI: 10.1007/s11332-021-00871-3
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: COVID‑19 nationwide lockdown and physical activity profiles among North‑western Italian population using the International Physical Activity Questionnaire (IPAQ)

Abstract: The Ref. [13] has been incorrectly published in the original publication. The complete correct reference is given below.Chen P, Mao L, Nassis GP, Harmer P, Ainsworth BE, Li F (2020) Coronavirus disease (COVID-19): the need to maintain regular physical activity while taking precautions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Presented study aimed to investigate levels of physical activity of female students from Slovakia and the Czech Republic. Physical activity levels are experiencing a downward trend, which has been supported by multiple research [24,25]. At the time of collecting the answers from our participants, there was an ongoing pandemic of Covid-19, which has affected lives of every member of society.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Presented study aimed to investigate levels of physical activity of female students from Slovakia and the Czech Republic. Physical activity levels are experiencing a downward trend, which has been supported by multiple research [24,25]. At the time of collecting the answers from our participants, there was an ongoing pandemic of Covid-19, which has affected lives of every member of society.…”
Section: Discussionmentioning
confidence: 69%
“…From the point of view of statistical evaluation, when evaluating the answers of girls from the Czech and Slovak Republics, we found significant differences at the level of significance p <0.01 (p = 2,767 E-06). Authors argue that improving health is driven by behavioural change and not by technological and scientific innovation [24]. In contrast, a recent study by Glynn et al [4] points to the importance and use of new technologies and adds that new technologies (mobile phones, smartphones) can have a major impact on changes in behavioural activity.…”
Section: Fig 1 Type Of Phone Owned By Adolescentsmentioning
confidence: 99%
“…Although it should also be mentioned that there were reports that spoke of greater PA in men (Abate Daga et al, 2021) or a similar decline in PA as in women (Christensen et al, 2022) and argued that family discouragement was a significant barrier for both men and women (Girgin & Okudan, 2021) -indicating the need for further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in sedentary behavior and sitting time was also observed [14,18]. However, a study among Italians residing in the northwestern region of the country showed a moderate level of PA during a nationwide-imposed lockdown [19]. Although some of the studies conducted during the COVID-19 period included Lebanon [14,17], there is a lack of data extensively assessing PA during lockdown in the country.…”
Section: Introductionmentioning
confidence: 99%